2022
DOI: 10.29219/fnr.v66.8282
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds of pequi pulp and oil extracts modulate antioxidant activity and antiproliferative activity in cocultured blood mononuclear cells and breast cancer cells

Abstract: Background: Pequi (Caryocar brasiliense Camb.) is a fruit from Brazilian Cerrado rich in bioactive compounds, such as phytosterols and tocopherols, which can modulate the death of cancer cells. Objective: In the present study, the main bioactive compounds of hydrophilic and lipophilic extracts of pequi oil and pulp were identified and were verified if they exert modulatory effects on oxidative stress of mononuclear cells cocultured with MCF-7 breast cancer cells. Study design: Identification and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is worth noting that inflammation in the lungs and their structures often involves oxidative stress associated with tissue damage [ 41 , 42 ]. In this context, the antioxidant bioactive compounds found in pequi oil, such as carotenoids and phenolic compounds [ 6 , 48 ], may also contribute to the observed anti-inflammatory effects in the models of airway diseases examined by Junior and colleagues (2020) and Coutinho and colleagues (2020) [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that inflammation in the lungs and their structures often involves oxidative stress associated with tissue damage [ 41 , 42 ]. In this context, the antioxidant bioactive compounds found in pequi oil, such as carotenoids and phenolic compounds [ 6 , 48 ], may also contribute to the observed anti-inflammatory effects in the models of airway diseases examined by Junior and colleagues (2020) and Coutinho and colleagues (2020) [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pequi oil is rich in antioxidants like carotenoids, vitamin E, and polyphenols. Due to this, numerous studies have investigated the use of the oil in preventing cell damage from oxidative stress [ 6 , 19 , 48 , 56 ]. In a study conducted by Vale (2019), it was demonstrated that supplementation with pequi oil could attenuate the oxidative stress induced by physical exercise in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of the extracts against MCF7 cells along with coculture illustrated that they possessed cytotoxic actions. Thus Moraes Brito., et al [8], concluded that pequi extracts possessed anticarcinogenic actions with pequi pulp possessing greater immunomodulation properties [8] (Figure 1-3).…”
Section: Mcf7 Cells Along With Coculture Of Mn Cells As Well As Mcf7 ...mentioning
confidence: 99%
“…Other than their cardiovascular in addition to robust antioxidant effects tocopherols along with phytosterols might further possess anticancer characteristics that have been illustrated in prior studies [7]. Thus Moraes Brito., et al [8], with the objective of identifying the basic agents present in Pequi pulp in addition to oil (hydrophilic as well as lipophilic) besides validating their modulatory actions on Oxidative stress (OS) of peripheral blood mononuclear cells which got cocultured with MCF7 breast cancer cells. Regarding identification in addition to quantification of the major bioactive agents of Pequi pulp in addition to oil (hydrophilic as well as oil lipophilic) extracts were carried out with utilization of liquid chromatography which is coupled with tandem liquid chromatography mass spectrometry (MS) (LC-MS/MS), whereas the anti-oxidant capability in vitro was estimated by utilization of approaches dependent on single electron transport reaction or hydrogen atom transfer, whereas for anti-oxidant along with anti-proliferative effects ex vivo enrolment of 20 healthy volunteers was done.…”
mentioning
confidence: 99%
“…The most commonly used technique for the identification and quantification of carotenoids is ultraviolet-visible spectrophotometry (UV-Vis) [31], and for phenolic compounds, it is high-performance liquid chromatography (HPLC) [32]. The main carotenoids and phenolic compounds identified in pequi fruit and some of its derivatives are listed in Table 3.…”
Section: Pequimentioning
confidence: 99%